Experimental traumatic effects about myelinated fibers in the spinal cord - Vaquero Crespo, J.; Oya, S.; Ramiro, M. (Investigación Clínica, 2013)
The authors report the histopathological alterations that take place in the nervous fibers of the contused spinal cord, particularly during the following 8 days of the experimental trauma. The axonal degeneration process can be quickly detected in the electronic and optic microscope. Particularly, the images of the axonal denudation and demyelinization which appear between the 4th and 8th day, with an important and persistent tissulary oedema.